2000
DOI: 10.1177/154193120004402247
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Task Performance, Reaction Time, and Perceived Urgency in Nonverbal Auditory Warnings

Abstract: Two experiments arc described in which participants were required to respond to auditory warnings known to vary in their perceived urgency. In the first, they simply responded to a warning of high, medium or low urgency whilst performing a simultaneous tracking task. Responses to the high urgency warning were faster than to the others. In the second experiment participants carried out an addition task on hearing the warning, and tbe warnings were either matched or mismatched to the difficulty of the task. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…This result extends existing work like [4,5] by testing in the context of a driving simulator and using all combinations of Audio, Visual and Tactile modalities. More urgent warnings created more quick and more accurate responses in this study.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…This result extends existing work like [4,5] by testing in the context of a driving simulator and using all combinations of Audio, Visual and Tactile modalities. More urgent warnings created more quick and more accurate responses in this study.…”
Section: Discussionsupporting
confidence: 53%
“…In line with [4,5], it was hypothesized that the designed urgency and modality of warnings would influence their recognition time. As in Experiment 1, all responses were acquired both in the presence and in the absence of a driving simulator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The goal was to investigate the effect of the situation simulated on observed driver responses. As described above, several studies have reported how designed urgency and modality affected response times, for example [8,11,27]. The influence of modalities used in warnings to lateral deviation and steering angle has also been shown in the past, for example in [21].…”
Section: Situational Urgency Experimentsmentioning
confidence: 99%
“…Edworthy, Loxley & Dennis [9] showed that higher fundamental frequency, higher speed and larger pitch range can increase the perceived urgency ratings of auditory warnings. Edworthy et al [8] observed significantly lower response times for highly urgent warnings, compared to warnings designed to be of medium and low urgency levels. Marshall, Lee & Austria [24] demonstrated how parameters like higher pulse duration and lower interpulse interval increased ratings of urgency of audio alerts.…”
Section: Guidelines For Warning Urgency Designmentioning
confidence: 99%